Efficient CO2 Removal for Ultra‐Pure CO Production by Two Hybrid Ultramicroporous Materials. Issue 13 (22nd February 2018) - Chen, Kai‐Jie; Yang, Qing‐Yuan; Sen, Susan; Madden, David G.; Kumar, Amrit; Pham, Tony; Forrest, Katherine A.; Hosono, Nobuhiko; Space, Brian; Kitagawa, Susumu; Zaworotko, Michael J.
Abstract: Removal of CO2 from CO gas mixtures is a necessary but challenging step during production of ultra‐pure CO as processed from either steam reforming of hydrocarbons or CO2 reduction. Herein, two hybrid ultramicroporous materials (HUMs), SIFSIX‐3‐Ni andTIFSIX‐2‐Cu‐i, which are known to exhibit strong affinity for CO2, were examined with respect to their performance for this separation. The single‐gas CO sorption isotherms of these HUMs were measured for the first time and are indicative of weak affinity for CO and benchmark CO2 /CO selectivity (>4000 forSIFSIX‐3‐Ni ). This prompted us to conduct dynamic breakthrough experiments and compare performance with other porous materials. Ultra‐pure CO (99.99 %) was thereby obtained from CO gas mixtures containing both trace (1 %) and bulk (50 %) levels of CO2 in a one‐step physisorption‐based separation process. Abstract : Benchmark CO2 /CO selectivity under ambient conditions has been observed in two hybrid ultramicroporous materials, thanks to much weaker interactions towards CO versus CO2 . Ultra‐pure CO (>99.99 %) can thereby be produced efficiently from gas mixtures containing CO2 impurities (1 % and 50 %) in a one‐step separation process using a fixed‐bed column of adsorbent.